A neglected population: Sexual and reproductive issues among adolescent and young Venezuelan migrant women at the northwestern border of Brazil. Issue 1 (22nd July 2021) - Soeiro, Rachel E.; Rocha, Leila; Surita, Fernanda G.; Bahamondes, Luis; Costa, Maria L.
Abstract: Objective: Adolescent and young women (10–24 years old) are a neglected group in humanitarian settings and their sexual and reproductive health (SRH) needs are habitually ignored. Our study aims to assess main SRH issues affecting migrant Venezuelan adolescents and young women in Boa Vista, Roraima at the northwestern border of Venezuela‐Brazil. Methods: A cross‐sectional study with a self‐responded questionnaire with information about SRH was conducted in 153 Venezuelan adolescent and young migrant women at Boa Vista, from January 18 to 23, 2021. A descriptive analysis was performed. Results: Mean age was 17.7 years and two‐thirds were under 20 years old. The majority (84%) were living on the streets. Most of them (54%) reported that they had at least one previous childbirth, 10% were pregnant at the time of the interview, 30% of them were not attending prenatal care. The main SRH concern was contraception (35%); however, 75% of those interviewed who went to a healthcare service were unable to obtain the method of their choice and for 91% no other contraceptive was offered. Conclusion: Migrant Venezuelan adolescents and young women in Boa Vista have their SRH needs overlooked. Efforts to address these SRH needs, especially during the pandemic, require urgent attention. Abstract : Adolescent and young adult Venezuelan migrant women are a neglected group in humanitarian settings.